THE MEDIATING ROLE OF SOCIAL INTERACTIVITY BETWEEN CONSUMER ENGAGEMENT BEHAVIOR AND BRAND LOYALTY ON LOCAL PRODUCT IN INDONESIA - Arthur Aledhean; Kurniawati Kurniawati; Bernardin Prasetyo Utomo; Nicolas Prasetyo Utomo (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract - This study aims to analyze the effect of consumer engagement behavior on brand loyalty mediated by social interactivity. The phenomenon that occurs is that the intensity of the use of media social in Indonesia is still not able to increase the competitiveness of Indonesian local products. This study use three dimensions on the variables of consumer engagement behavior then social interactivity and brand loyalty as research variables, yet local fashion brand as research object. The sample determined by puposive sampling method was 170 respondents. Data analysis technique uses Structural Equation Model (SEM) supported by AMOS version 21. The result show that the mediation of social interactivity partially influences consumer engagement behavior on brand loyalty, which means consumer engagement behavior can affect brand loyalty either with or without mediation of social interactivity. This study does not categorize brands so that they are not competitively equivalent to brands, then there is no cultural interaction that is considered in interpreting consumer engagement behavior. Keywords: Brand Loyalty; Consumer Engagement Behavior; Social Interactivity